ANALISA SISTEM OPERASI DAN DAYA PRODUKSI PEMBANGKIT LISTRIK TENAGA AIR KAPASITAS 7,5 MW DI PLTA PARAKAN KONDANG - Selamet Nurjaman, Ade; Susandi, Dony (Universitas Majalengka, 2019)
One of the energy needs that may be almost inseparable in human life at this time is the need for electrical energy. as is known to obtain electrical energy through a long and complicated process, but given the nature of this electrical energy that is easily channeled and easy to convert into other forms of energy such as light energy, heat energy, chemical energy, mechanical energy, sound, images , etc. Electric energy utilization has been widely used for household, commercial, government, industrial and so on. Indonesia Power UBP Saguling Parakan Kondang Hydroelectric Power Plant (PLTA) is one of the power plants that is able to meet the electricity needs of Java-Bali with the source of generation coming from water. To meet the electricity needs of Java - Bali, each plant will try to minimize errors in each production process. One of them is by analyzing the operating system and production power at each plant so that the targeted production power can be achieved, as well as the Parakan Kondang Hydroelectric Power Plant. Parakan Kondang Hydroelectric Power Plant (PLTA) always implements